Protease-activated receptor-2 (PAR-2) regulates enterotoxigenic Escherichia coli-induced diarrhea during weaning in piglets - Xiao-ying Pei; Ding-zong Guo; Dong-hai Zhou; Rui Guo (African Journal of Pig Farming, 2015)
Protease-activated receptor-2 (PAR-2) is a member of the G-protein-coupled receptor family. The proteases that activate PAR-2 are released during inflammation and injury, with PAR-2 regulating the response to these insults. In the gastrointestinal tract, PAR-2 is known to alter gastrointestinal secretion, motility, inflammation, and pain. In many cases, PAR-2 has been reported as proinflammatory and proliferative. Paradoxically, PAR-2 is also suggested to be anti-inflammatory in some instances. Weaning piglet diarrhea is severely detrimental to the porcine industry, being responsible for 11% of total piglet deaths, while those that survive from the disease experience developmental problems and fail to grow to the size of their healthy counterparts. Thus, we sought to determine any correlation between PAR-2 and weaning diarrhea. We hypothesized that PAR-2 might represent a new target in the treatment of weaning diarrhea. The current study measured PAR-2 using immunohistochemistry on sections of piglet gastrointestinal tract mucosa and identified changes in receptor expression during the development and course of weaning. Moreover, the effect of PAR-2 stimulation using lipopolysaccharide (LPS) and heat-labile enterotoxin (LT) on IL-6 and IL-8 production in pig intestinal epithelial cells (IEC) was determined. This study found that PAR-2 is expressed abundantly in the piglet gastrointestinal tract mucosa, and revealed that PAR-2 mRNA and protein expression are both correlated with the severity of diarrhea. The generation of IL-6 and IL-8 by IECs was significantly increased following stimulation with PAR-2 agonists dose-dependently. Thus, we suggest PAR-2 may be involved in the development of diarrhea during weaning in piglets.